1991
DOI: 10.1111/j.1439-0450.1991.tb00845.x
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Changes in Lymphocyte Function of Dairy Calves

Abstract: Lymphocyte blastogenic response, B-lymphocyte population and antibody-producing activity of lymphocytes were determined to evaluate the lymphocyte function in neonatal calves during the first 4 weeks of life. The mean percentage of B-lymphocytes ranged from 10.2 to 12.5 % during the first 14 days of life and from 15.3 to 17.5% in calves from the day 21 to day 28 after birth. The absolute number of B-lymphocytes increased significantly (P< 0.05) from 370/p1 at birth to 736/p1 on day 28 after birth. The mean sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 9 publications
3
13
0
Order By: Relevance
“…These younger animals would be expected to have decreased capability for defence against microbial infections. Values determined for leucocyte parameters including total WBC, neutrophil and lymphocyte counts tended to be similar to those reported by Tennant et al (1974), but were greater than corresponding values, reported by Nagahata et al (1991). The latter study reported a significant decrease in WBC count on postnatal day 3; despite differences in the two study designs, we also observed a significantly lower WBC count in calves aged 3-7 days compared to older calves.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…These younger animals would be expected to have decreased capability for defence against microbial infections. Values determined for leucocyte parameters including total WBC, neutrophil and lymphocyte counts tended to be similar to those reported by Tennant et al (1974), but were greater than corresponding values, reported by Nagahata et al (1991). The latter study reported a significant decrease in WBC count on postnatal day 3; despite differences in the two study designs, we also observed a significantly lower WBC count in calves aged 3-7 days compared to older calves.…”
Section: Discussionsupporting
confidence: 84%
“…A previous study has suggested that higher plasma cortisol levels present in neonatal calves inhibited B-cell transformation and observed that B-cell numbers increased markedly at 21 12 L.J. Allen et al days after birth (Nagahata et al 1991). Similarly in our study, calves aged 21 days and older (group D) had significantly higher B-cell counts than younger calves.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Low concentrations of Cp were reported at birth, which increased in the fi rst days of life, infl uenced by response to birth or related to the activity of the liver [35]. Hepatic production of acute phase proteins is one of the mechanisms involved in the compensation of a functionally immature immunological system during the early neonatal period, which facilitate adaptation to extrauterine life [9]. Higher concentrations of acute phase proteins in calves can be explained also by the infl uence of other stressors, infections or various infl ammatory diseases (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Functional immaturity of neonatal lymphocytes was reported during the fi rst weeks of life [9]. Thus, colostral transfer of immune components to obtain passive immunity and an effective non-specifi c immune response may be important for the adaptation to the extra-uterine life [10].…”
Section: Introductionmentioning
confidence: 99%